GRASI DALAM KASUS NARKOTIKA DI ANTARA KEBIJAKAN KEADILAN DAN UPAYA PENEGAKAN HUKUM - Puluhulawa, Irlan (LPPM STIH Awang Long, 2024)
This research examines the process of giving mercy to drug prisoners and if it supports criminal law's drug crime prevention goals. Drug offences in Indonesia are regarded extreme crimes that destroy social order and affect the younger generation, hence they are generally sentenced to death or life in prison. The President's power under Article 14 paragraph (1) of the 1945 Constitution and Law No. 22 of 2002 respecting Clemency allows offenders to request clemency. Granted pardon to drug offenders creates a conflict between severe law enforcement to prevent and rehabilitation and social reintegration. This research employs normative, statutory, and juridical-analytical methods. The 1945 Constitution, Law No. 22 of 2002 on Clemency, and Law No. 35 of 2009 on Narcotics, as well as court rulings on drug clemency, are examined in this paper. To understand how mercy is applied to drug offences, retributive, utilitarian, and rehabilitative philosophies of punishment were examined. This research found that although clemency may help rehabilitate offenders, it might also impair drug crime deterrence. To prevent reoffending, drug clemency must be backed by a thorough rehabilitation program and based on tougher and more open standards. Thus, clemency policy change is required to reconcile justice, prevention, and rehabilitation in Indonesian criminal law.